Antik Kilikya Kenti Prakana’nın Konumu Hakkında Düşünceler / Thoughts on the Location of the Ancient Cilician City of Prakana - Ayhan YALÇIN (Arkhaia Anatolika, 2022)
One of the main problems of Ancient Greek and Roman archaeology in Rough Cilicia is that it is not known exactly where some ancient settlements with known names will be located. In this context, it is stated in the ancient sources that the settlement called Prakana is somewhere between the city of Claudiopolis (Mut) and the cities of Seleukeia pros to Kalykadno (Seleucia ad Calycadnum / Silifke). However, apart from this general information, the exact location of the settlement is unknown. In this article, it is questioned that Prakana was placed in the city of Diocaesareia (today’s Uzuncaburç) with a general acceptance, especially based on what Ramsay wrote in 1890, and that this name was the old name of Diocaesareia. The actual location of Diocaesareia during the years of Ramsay’s writing is not yet known. For this reason, Ramsay takes the narratives in ancient sources as a criterion. In addition, the priest who attended the Second Council of Nicaea relies on information about Manzon in 787. According to this information, Manzon is the representative of Prakana and Diocaesareia. Based on this information, Ramsay accepts Diocaesareia and Prakana as the same settlement. Regarding Ramsay’s proposals for the location of Diocaesareia, Heberdey and Wilhelm in 1896, what can be argued for the moment with certainty whether Diocaisareia, which should have been located on the road from Laranda to Seleuceia, should be placed here (on the ground on Ramsay’s map). Nor does it say it can be refuted. Later, when the inscription on the city gate was read by Bauer in 1914, it was understood that Uzuncaburç was Diocaesareia. In this case, according to our source research and historical information, it is not possible for Prakana to be in Diocaesareia. According to the information in the historical sources that give a clue to its geographical location, Prakana should have been located around today’s Zeyne on the Mut – Gülnar road. Therefore, the name Prakana is not the old name of Diocaesareia.